2022
DOI: 10.4314/dujopas.v7i3b.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Schistosomiasis in Warwade Community, Jigawa State, Nigeria

Abstract: There is currently no documented literature on the status of transmission of schistosomiasis in Warwade community situated near a dam. This study was designed to determine the prevalence of schistosomiasis in the community. A total of 300 urine and stool samples from randomly selected participants were analysed for S. haematobium and S. mansoni using sedimentation and kato-katz techniques respectively. A pre-tested structured questionnaire was administered to all the participants and in the case of minors thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
1
Order By: Relevance
“…These result confirmed that malaria continues to be a major cause of morbidity in Kano State. Consistent with the present study, previous studies (e.g Shuaibu et al, 2017;Moise and Robert, 2017;Babamale et al, 2018;Nnamonu et al, 2020) conducted in Jigawa, Kwara, Enugu, and Bauchi States also reported high prevalence of malaria among study subjects, with rates of 63.7% (300/471), 64.8% (5,115/7,899), and 35.8% (118/330), respectively.…”
Section: Prevalence Of Malariasupporting
confidence: 92%
“…These result confirmed that malaria continues to be a major cause of morbidity in Kano State. Consistent with the present study, previous studies (e.g Shuaibu et al, 2017;Moise and Robert, 2017;Babamale et al, 2018;Nnamonu et al, 2020) conducted in Jigawa, Kwara, Enugu, and Bauchi States also reported high prevalence of malaria among study subjects, with rates of 63.7% (300/471), 64.8% (5,115/7,899), and 35.8% (118/330), respectively.…”
Section: Prevalence Of Malariasupporting
confidence: 92%
“…The high prevalence and infection intensity in schoolchildren in the area is an indicator that the rest of the population are at high risk of infection. The 50.9% prevalence of urogenital schistosomiasis in Warwade is greater than the prevalence reported by Alhaji et al 26 who found a 12.3% prevalence in the Warwade community using a sedimentation technique. This difference is because we sampled primary schoolchildren and adolescents and employed a filtration technique.…”
Section: Discussioncontrasting
confidence: 57%